Efektivitas Permainan Acak Kata Dengan Flashcard Untuk Keterampilan Berbicara Bahasa Arab Kelas XI SMA IT Bina Amal Kota Semarang: The Effectiveness of Random Word Games with Flashcards for Arabic Speaking Skills of Class XI SMA IT Bina Amal Semarang City - Wafiq Azizatunni'mah; Muchlisin Nawawi (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
The aim of this study is to describe the implementation and determine the effectiveness of flashcard media combined with a word scramble game for teaching Arabic speaking skills to 11th-grade students at Integrated Islamic Senior High School Bina Amal, Semarang. Flashcard media and the word scramble game were chosen because they are believed to stimulate students' interest in learning and improve their memory in Arabic language learning, especially speaking skills. The type and design of this study is a quantitative experimental approach, involving 24 students as the sample. Data collection techniques included tests (pre-test and post-test) and non-tests such as interviews, questionnaires, and documentation. The data analysis techniques used were the Shapiro-Wilk normality test, N-Gain scores, and hypothesis testing (T-test). The results of the study show that the word scramble game using flashcards is effective in improving Arabic speaking skills. This is evidenced by an increase in the average score from 78.08 in the pre-test to 84.25 in the post-test, with an N-gain score of 3.72, indicating a moderate level of improvement. Additionally, the Shapiro-Wilk normality test showed a normal data distribution, and the paired sample t-test resulted in a significance value of <0.05, indicating a significant effect from the intervention. This research contributes both theoretically and practically to Arabic language learning. Practically, this game can be used by teachers as a solution to increase students' interest in speaking skills. Furthermore, this study can serve as a reference for researchers who wish to explore similar methods or develop them for other language skills.